2010
DOI: 10.1007/s12555-010-0304-7
|View full text |Cite
|
Sign up to set email alerts
|

A biologically inspired improvement strategy for particle filter: Ant colony optimization assisted particle filter

Abstract: Particle Filter (PF) is a sophisticated model estimation technique based on simulation. Due to the natural limitations of PF, two problems, namely particle impoverishment and sample size dependency, frequently occur during the particles updating stage and these problems will limit the accuracy of the estimation results. In order to alleviate these problems, Ant Colony Optimization is incorporated into the generic PF before the updating stage. After executing the Ant Colony optimization, impoverished particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…PF provides an approximate solution for the discrete-time recursive updating of the posterior probability density function p(λ t |y 1:t ) [36]. Under PF, the posterior distribution of λ t is approximated by a collection of weighted particles λ t = {λ n t , w n t } N n=1 .…”
Section: Introductionmentioning
confidence: 99%
“…PF provides an approximate solution for the discrete-time recursive updating of the posterior probability density function p(λ t |y 1:t ) [36]. Under PF, the posterior distribution of λ t is approximated by a collection of weighted particles λ t = {λ n t , w n t } N n=1 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the application of different evolutionary optimization algorithms in various scenarios [16][17][18], some researchers have studied them in combination with visual tracking problems and made significant progress. By combining an evolutionary optimization algorithm with the particle filter, the researchers [19,20] found that the evolutionary algorithm does not depend on the prior knowledge of the particle filter, and can be explored and exploited in the face of uncertainty so that the particles show arbitrariness. Based on this characteristic, it can improve the particle impoverishment problem by combining the particle filter with an evolutionary optimization algorithm.…”
Section: Improved Particle Filter Based On Sample Impoverishmentmentioning
confidence: 99%
“…In recent years, researchers worked extensively on this topic. Many algorithms, such as particle swarm algorithms [21][22][23][24][25][26], ant colony algorithms [27][28][29][30][31][32], genetic algorithms [33][34][35][36][37][38], and bat algorithms [39][40][41][42][43][44], have made great developments and attracted more and more attention, especially in the field of solving path planning problems in obstacle environments. UAVs perform firefighting tasks in forest fire areas, and the actual trajectory of UAVs in forest firefighting must be processed based on the appropriate trajectory generation algorithms in conjunction with the characteristics of the UAV itself and the environmental characteristics to ensure that the final trajectory matches the dynamics of the UAV [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%